Analysis and comparison of a customize infant incubator chamber shape using finite element method - Somsri Daochai (2018)
The infant incubator is an essential medical device for a new born whose weight is lower than a standard level or early birth. In general, many parameters such as air temperature, air circulation, humidity, oxygenation, noise level and sterilization must be controlled strictly all over an operation range. In this paper, we presented an analysis of heat transfer and air flow circulation in chamber hood by comparing between 2 different design chambers as a semi-hexagonal hood and a dome hood. COMSOL Multiphysic3.3, a three dimensional simulation program was used in our experiment which basing on fluid dynamics and convective heat transfer equation. The simulation was performed under normal room circumstance at 25. The results show that a thermal distribution and air circulation of dome hood are quite better than semi-hexagonal hood noticeably . © 2008 IEEE.